The Determinants of the Ict- Based O/Dl Program to Encourage and Support the Countrys Economy - *, Slameto (Sebelas Maret University, 2016)
This research question is formulated as follows: 1). How is the success rate of Satya Wacana Christian University ICT-based O/DL program to encourage and support the countrys economy? 2). what are the factors that determine (determinant) the success of ICT-based ODL program to encourage and support the countrys economy? This study was conducted on the basis of the ITEP alumni assessment. The data sources are 52 ITEP graduates; Data were collected through a self-rating scale consisting of 30 items that have been proven valid and reliable; Data analysis used descriptive analysis and stepwise multiple regression models with SPSS for windows version 20. The performance the Satya Wacana Christian University ICT-based ITEP support and encourage the countrys economy is at the high and very high level. There are three determinants of the success of the performance of the ITEP: 1) Lecturer Professionalism, Curriculum Development, and the Metacognitive, giving the influence variable of 78.30%. Other variables, namely, Leadership, Achievement Class, Networked Systems, Adoption of ICT into Teaching Learning Processes and Active, Creative, Joy Full and Effective Learning/ACJEL which are supported by the data do not affect the performance and success of conducting ITEP Distance Learning in the attempts to support and encourage the countrys economy. Therefore, the development of distance learning should be focused on the lecturer; promoting lecturer is a more critical factor and it should be professionally based, such as curriculum developers and actors of teaching-learning process.